Parenting and Social Development on Early Childhood Emotions - Harahap, Hanni Holila; Arlinda, Shabrina; Mulyana, Hilma (International Journal Labs, 2022)
Parenting patterns carried out by parents have several real impacts on every aspect of child development, one of which is social and emotional development. The purpose of this study is to see how closely the relationship between parenting and social development is on the emotional aspects of early childhood. The methodology used in this research is quantitative with a correlational design, 42 respondents are in Kebarepan Plumbon Village, Cirebon Regency. The influence of parenting applied can make children easy to work with their friends, willing to share with friends, being able to help friends, being honest, giving permission when children want to go to the toilet and being able to care for their friends. The correlation coefficient figure obtained is equal to indicating that all variables have a high relationship. Where the research results Ho is rejected and Ha is accepted in other words that there is a significant positive relationship between parenting and social development on emotional early childhood in Kebarepan Plumbon Village, Cirebon Regency.